The potential of arbuscular mycorrhizal fungi to improve soil organic carbon in agricultural ecosystems: A meta‐analytical approach - Conti, Georgina (2025)
1. Increasing soil organic carbon (SOC) in agroecosystems is a key objective forenhancing agricultural sustainability and mitigating climate change. Arbuscularmycorrhizal fungi (AMF) can increase yield and provide several other ecosystemservices. Still, studies conducted in agricultural soils have shown that their effectson SOC can be either positive, neutral or negative. In this study, we conducteda quantitative review of the literature to evaluate the role of AMF in influencingSOC across various crop species and conditions.2. Through a systematic search of publications, we compiled a dataset comprising62 trials from 19 studies including field and pot experiments that directlymanipulated the mycorrhizal status of plants. We conducted a meta-analysis toquantitatively evaluate the role of AMF on SOC across several crop species andconditions.3. We found an overall positive effect of AMF on SOC, with an average increaseof 21.5%. However, this positive effect was statistically significant only in potexperiments whereas in field experiments, the effect was mainly modulated bytexture and organic matter content. The effect of AMF on SOC did not vary withcrop species´ functional type, AMF inoculation sources (single or mixed AMFspecies) or other soil variables considered4. Our results highlight the significant potential for AMF-mediated mechanisms topromote SOC accumulation in agricultural soils, although this effect is contextdependent. However, future research with different approaches and scales isneeded to evaluate the impact of AMF on SOC dynamics in agricultural systemsand elucidate the mechanisms behind their contribution to SOC accrual.